AN IDENTIFICATION SYSTEM FOR NON-COMMERCIAL ORGANIZATIONS FOR TAX ADMINISTRATION PURPOSES - A. V Gryshchenko (Финансы: теория и практика)
Political and economic changes occurring in Russia in the past decades caused the emergence of new legal forms and concepts including non-commercial organizations. The discussion of the need to improve the system of tax control over non-commercial organizations has been going on for a while. The paper analyzes the national legislation concerning non-commercial organizations and makes a conclusion that at present an effective system of identifying non-commercial organizations for the purposes of tax administration does not exist. The financial statements of non-commercial organizations based on the SPARK database have been studied; a system of identification of non-commercial organizations through the unification of legal forms of non-commercial organizations and bringing the latter to a finite number of types: conventionally profitless non-commercial and profitable non-commercial organizations are proposed.